USA: from the invention of terrorism to the “preventive war” - Almeida, José Rubens Mascarenhas de (Universidade Estadual Paulista / UNESP, 2010)
The present article analyzes some aspects of the American imperialism, mainly in what concerns the state terrorism, leaving of ideological aspects contained in the politics that say to combat it. It emphasizes the paper of the State and their imperial tentacles-terrorists, among these the great transnational corporations and the multilateral institutions in the powder-II World war.